Social network analysis. - Scott, John (SAGE Publications, 2017)
This classic, best-selling text introduces newcomers to the key theories and techniques of social network analysis, while also guiding more experienced analysts through their own research. Incorporating the most important and cutting-edge developments in the field, this new Fourth Edition is thoroughly expanded and up-to-date, featuring a new chapter on data collection and updated examples reiterating the continued importance of social network analysis in an increasingly interconnected world.--Publisher's description.